If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -2) + 10 = 10 Reorder the terms: x(-2 + x) + 10 = 10 (-2 * x + x * x) + 10 = 10 (-2x + x2) + 10 = 10 Reorder the terms: 10 + -2x + x2 = 10 Add '-10' to each side of the equation. 10 + -2x + -10 + x2 = 10 + -10 Reorder the terms: 10 + -10 + -2x + x2 = 10 + -10 Combine like terms: 10 + -10 = 0 0 + -2x + x2 = 10 + -10 -2x + x2 = 10 + -10 Combine like terms: 10 + -10 = 0 -2x + x2 = 0 Solving -2x + x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-2 + x) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-2 + x)' equal to zero and attempt to solve: Simplifying -2 + x = 0 Solving -2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + x = 0 + 2 x = 0 + 2 Combine like terms: 0 + 2 = 2 x = 2 Simplifying x = 2Solution
x = {0, 2}
| 0.1x^2+16x-100=0 | | 2t+a=19 | | 8x^2-8=6x | | X-6y=38 | | w^2-4w=32 | | 1/8=3r/4 | | c/-8=-14 | | 2.3=b/4 | | (1-(2/3x))/(x-(4/9x)) | | -2=6(v-3)-8v | | 36=(7w-4)/2+(9w-2)/7 | | 36=7w-4/2+9w-2/7 | | 6x+30=10x+30 | | 6a+5=2a+3 | | 4=2x+8/10 | | 100-4q=10+2q | | 4x+3(x-2)=78 | | 2x+4y-7= | | 48q^2-600q+24=0 | | (p/-6)+7=16 | | -8r^2+64r+19=0 | | 2x-(4+1)+2= | | 13/5+41/5 | | 3x-32=-7x+38 | | 1.2x+4.4=0.8x-5.1 | | 6x-3(5x+2)=4-5x | | 5.2x(2x+4)=30 | | 7x+24=-4 | | 5.2x+4=30 | | (8-17)+3= | | 6b-(b-3)=56 | | (8x-17)+3= |